A Cable‐Actuated Soft Manipulator for Dexterous Grasping Based on Deep Reinforcement Learning - Kunyu Zhou; Baijin Mao; Yuzhu Zhang; Yaozhen Chen; Yuyaocen Xiang; Zhenping Yu; Hongwei Hao; Wei Tang; Yanwen Li; Houde Liu; Xueqian Wang; Xiaohao Wang; et al. (Advanced Intelligent Systems, 2024)
The growing interest in the flexibility and operational capabilities of soft manipulators in confined spaces emphasizes the need for precise modeling and accurate motion control. Conventional control methods encounter difficulties in modeling and involve intricate computations. This work introduces a novel deep reinforcement learning (DRL) control algorithm based on neural network modeling. Using the Whale Optimization Algorithm, an approximate dynamic model for the soft manipulator is established. The twin delayed deterministic policy gradient is employed for DRL control. Domain randomization is applied during pretraining in a simulated environment. The algorithm addresses issues related to dependency on measurement data quality and redundant mappings, outperforming other methods by 8–15 mm in control accuracy. The trained DRL controller achieves precise trajectory tracking within the soft manipulator's task space, enabling successful grasping tasks in various complex environments, including pipelines and other narrow spaces. Experimental results confirm the autonomy of our controller in performing these tasks without human intervention.